Niotsi edetle konde nezo tingi [electronic resource] : St. Matthew, St. Mark, St. Luke, St. John, Kogade. - Spendlove, W.; British and Foreign Bible Society. (London : British and Foreign Bible Society, 1905)
On t.p. verso: The Four Gospels in the Slavi language of the Mackenzie River Indians, N.W. Territories, Canada / translated by W. Spendlove. Cover title: Four Gospels. Electronic reproduction. Mode of access: Internet. 44